Delivering Patient Data to Patients Themselves. Issue 1 (26th June 2018) - Ancker, Jessica S.
Physicians need nearly a decade of training to understand complex patient data such as laboratory tests and genomic data. How can these data possibly be delivered to patients in ways that they can understand and use?